Covering Bones: The Archaeology of Respect on the Kazan River, Nunavut - Friesen, T.; Stewart, Andrew (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2017)
Complex relationships between people and animals define life in the northern past. For Inuit these relationships are manifested in many ways, particularly in practices that are often described as showing respect for animals, thus promoting stable relations between animal and human societies. Frustratingly, many of these activities, which are so prominent in the ethnographic record, have few archaeological correlates. Here, we examine one important practice with a relatively high level of archaeological visibility: the concealment of caribou bones under stones and in other inaccessible areas, which thereby protect them from dogs and other disturbances that could offend the caribou’s inua (spirit, soul). We examine this phenomenon at several important caribou crossings and elsewhere at inland Inuit archaeological sites on the Kazan River, southern Nunavut, where we have conducted extensive surveys. This research was performed in collaboration with Baker Lake community members who have direct knowledge of these localities, including aspects of bone disposal. Together, these studies reveal a cultural landscape in which the human–caribou relationship is omnipresent, not just in terms of features relating to hunting and storage, but also with regard to the spiritual connection between these two interdependent categories of being.